![x^3y^2+\sin(x\ln y)+e^{xy}=0](https://tex.z-dn.net/?f=x%5E3y%5E2%2B%5Csin%28x%5Cln%20y%29%2Be%5E%7Bxy%7D%3D0)
Differentiate both sides, treating
as a function of
. Let's take it one term at a time.
Power, product and chain rules:
![\dfrac{\mathrm d(x^3y^2)}{\mathrm dx}=\dfrac{\mathrm d(x^3)}{\mathrm dx}y^2+x^3\dfrac{\mathrm d(y^2)}{\mathrm dx}](https://tex.z-dn.net/?f=%5Cdfrac%7B%5Cmathrm%20d%28x%5E3y%5E2%29%7D%7B%5Cmathrm%20dx%7D%3D%5Cdfrac%7B%5Cmathrm%20d%28x%5E3%29%7D%7B%5Cmathrm%20dx%7Dy%5E2%2Bx%5E3%5Cdfrac%7B%5Cmathrm%20d%28y%5E2%29%7D%7B%5Cmathrm%20dx%7D)
![=3x^2y^2+x^3(2y)\dfrac{\mathrm dy}{\mathrm dx}](https://tex.z-dn.net/?f=%3D3x%5E2y%5E2%2Bx%5E3%282y%29%5Cdfrac%7B%5Cmathrm%20dy%7D%7B%5Cmathrm%20dx%7D)
![=3x^2y^2+6x^3y\dfrac{\mathrm dy}{\mathrm dx}](https://tex.z-dn.net/?f=%3D3x%5E2y%5E2%2B6x%5E3y%5Cdfrac%7B%5Cmathrm%20dy%7D%7B%5Cmathrm%20dx%7D)
Product and chain rules:
![\dfrac{\mathrm d(\sin(x\ln y)}{\mathrm dx}=\cos(x\ln y)\dfrac{\mathrm d(x\ln y)}{\mathrm dx}](https://tex.z-dn.net/?f=%5Cdfrac%7B%5Cmathrm%20d%28%5Csin%28x%5Cln%20y%29%7D%7B%5Cmathrm%20dx%7D%3D%5Ccos%28x%5Cln%20y%29%5Cdfrac%7B%5Cmathrm%20d%28x%5Cln%20y%29%7D%7B%5Cmathrm%20dx%7D)
![=\cos(x\ln y)\left(\dfrac{\mathrm d(x)}{\mathrm dx}\ln y+x\dfrac{\mathrm d(\ln y)}{\mathrm dx}\right)](https://tex.z-dn.net/?f=%3D%5Ccos%28x%5Cln%20y%29%5Cleft%28%5Cdfrac%7B%5Cmathrm%20d%28x%29%7D%7B%5Cmathrm%20dx%7D%5Cln%20y%2Bx%5Cdfrac%7B%5Cmathrm%20d%28%5Cln%20y%29%7D%7B%5Cmathrm%20dx%7D%5Cright%29)
![=\cos(x\ln y)\left(\ln y+\dfrac1y\dfrac{\mathrm dy}{\mathrm dx}\right)](https://tex.z-dn.net/?f=%3D%5Ccos%28x%5Cln%20y%29%5Cleft%28%5Cln%20y%2B%5Cdfrac1y%5Cdfrac%7B%5Cmathrm%20dy%7D%7B%5Cmathrm%20dx%7D%5Cright%29)
![=\cos(x\ln y)\ln y+\dfrac{\cos(x\ln y)}y\dfrac{\mathrm dy}{\mathrm dx}](https://tex.z-dn.net/?f=%3D%5Ccos%28x%5Cln%20y%29%5Cln%20y%2B%5Cdfrac%7B%5Ccos%28x%5Cln%20y%29%7Dy%5Cdfrac%7B%5Cmathrm%20dy%7D%7B%5Cmathrm%20dx%7D)
Product and chain rules:
![\dfrac{\mathrm d(e^{xy})}{\mathrm dx}=e^{xy}\dfrac{\mathrm d(xy)}{\mathrm dx}](https://tex.z-dn.net/?f=%5Cdfrac%7B%5Cmathrm%20d%28e%5E%7Bxy%7D%29%7D%7B%5Cmathrm%20dx%7D%3De%5E%7Bxy%7D%5Cdfrac%7B%5Cmathrm%20d%28xy%29%7D%7B%5Cmathrm%20dx%7D)
![=e^{xy}\left(\dfrac{\mathrm d(x)}{\mathrm dx}y+x\dfrac{\mathrm d(y)}{\mathrm dx}\right)](https://tex.z-dn.net/?f=%3De%5E%7Bxy%7D%5Cleft%28%5Cdfrac%7B%5Cmathrm%20d%28x%29%7D%7B%5Cmathrm%20dx%7Dy%2Bx%5Cdfrac%7B%5Cmathrm%20d%28y%29%7D%7B%5Cmathrm%20dx%7D%5Cright%29)
![=e^{xy}\left(y+x\dfrac{\mathrm dy}{\mathrm dx}\right)](https://tex.z-dn.net/?f=%3De%5E%7Bxy%7D%5Cleft%28y%2Bx%5Cdfrac%7B%5Cmathrm%20dy%7D%7B%5Cmathrm%20dx%7D%5Cright%29)
![=ye^{xy}+xe^{xy}\dfrac{\mathrm dy}{\mathrm dx}](https://tex.z-dn.net/?f=%3Dye%5E%7Bxy%7D%2Bxe%5E%7Bxy%7D%5Cdfrac%7B%5Cmathrm%20dy%7D%7B%5Cmathrm%20dx%7D)
The derivative of 0 is, of course, 0. So we have, upon differentiating everything,
![3x^2y^2+6x^3y\dfrac{\mathrm dy}{\mathrm dx}+\cos(x\ln y)\ln y+\dfrac{\cos(x\ln y)}y\dfrac{\mathrm dy}{\mathrm dx}+ye^{xy}+xe^{xy}\dfrac{\mathrm dy}{\mathrm dx}=0](https://tex.z-dn.net/?f=3x%5E2y%5E2%2B6x%5E3y%5Cdfrac%7B%5Cmathrm%20dy%7D%7B%5Cmathrm%20dx%7D%2B%5Ccos%28x%5Cln%20y%29%5Cln%20y%2B%5Cdfrac%7B%5Ccos%28x%5Cln%20y%29%7Dy%5Cdfrac%7B%5Cmathrm%20dy%7D%7B%5Cmathrm%20dx%7D%2Bye%5E%7Bxy%7D%2Bxe%5E%7Bxy%7D%5Cdfrac%7B%5Cmathrm%20dy%7D%7B%5Cmathrm%20dx%7D%3D0)
Isolate the derivative, and solve for it:
![\left(6x^3y+\dfrac{\cos(x\ln y)}y+xe^{xy}\right)\dfrac{\mathrm dy}{\mathrm dx}=-\left(3x^2y^2+\cos(x\ln y)\ln y-ye^{xy}\right)](https://tex.z-dn.net/?f=%5Cleft%286x%5E3y%2B%5Cdfrac%7B%5Ccos%28x%5Cln%20y%29%7Dy%2Bxe%5E%7Bxy%7D%5Cright%29%5Cdfrac%7B%5Cmathrm%20dy%7D%7B%5Cmathrm%20dx%7D%3D-%5Cleft%283x%5E2y%5E2%2B%5Ccos%28x%5Cln%20y%29%5Cln%20y-ye%5E%7Bxy%7D%5Cright%29)
![\dfrac{\mathrm dy}{\mathrm dx}=-\dfrac{3x^2y^2+\cos(x\ln y)\ln y-ye^{xy}}{6x^3y+\frac{\cos(x\ln y)}y+xe^{xy}}](https://tex.z-dn.net/?f=%5Cdfrac%7B%5Cmathrm%20dy%7D%7B%5Cmathrm%20dx%7D%3D-%5Cdfrac%7B3x%5E2y%5E2%2B%5Ccos%28x%5Cln%20y%29%5Cln%20y-ye%5E%7Bxy%7D%7D%7B6x%5E3y%2B%5Cfrac%7B%5Ccos%28x%5Cln%20y%29%7Dy%2Bxe%5E%7Bxy%7D%7D)
(See comment below; all the 6s should be 2s)
We can simplify this a bit by multiplying the numerator and denominator by
to get rid of that fraction in the denominator.
![\dfrac{\mathrm dy}{\mathrm dx}=-\dfrac{3x^2y^3+y\cos(x\ln y)\ln y-y^2e^{xy}}{6x^3y^2+\cos(x\ln y)+xye^{xy}}](https://tex.z-dn.net/?f=%5Cdfrac%7B%5Cmathrm%20dy%7D%7B%5Cmathrm%20dx%7D%3D-%5Cdfrac%7B3x%5E2y%5E3%2By%5Ccos%28x%5Cln%20y%29%5Cln%20y-y%5E2e%5E%7Bxy%7D%7D%7B6x%5E3y%5E2%2B%5Ccos%28x%5Cln%20y%29%2Bxye%5E%7Bxy%7D%7D)
Answer:
area = 102 ft²
Step-by-step explanation:
(8x6) + (9x6) = 48 + 54 = 102 ft²
Answer:
mean= sum of the terms/ (over) number of terms
Answer:
111
Step-by-step explanation:
divide by 2 to find the radius